SINTESIS Zn-Al-EDTA HYDROTALCITE DAN APLIKASINYA SEBAGAI ADSORBEN ION Pb2+ - , DAHLIA ROSMA INDAH; , Dr. Roto, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Synthesis of Zn-Al-EDTA hydrotalcite and its application as adsorbent for Pb2+ ion have been studied. The aim of this research was to study the ability of Zn-Al-EDTA hydrotalcite as adsorbent of Pb2+ ion. Acidity condition, kinetics, and adsorption capacity along with characterization of Zn-Al-EDTA hydrotalcite solid crystal after adsorption and after desorption were studied. The Zn-Al hydrotalcite with nitrate anion in interlayer was first synthesized by coprecipitation method followed by hydrothermal treatment at 100Â°C for 15 h. The nitrate anion was exchanged with EDTA to yield Zn-Al-EDTA hydrotalcite. The Zn-Al-EDTA hydrotalcite was characterized using X-ray Difractometer (XRD) and Fourier Transform-Infra Red Spectrofotometer (FT-IR). Characterization of Zn-Al-EDTA hydrotalcite using XRD showed that the basal spacing d003 before and after ion exchange was 8.90 Ã and 14.52 Ã. The FTIR spectra suggested that C=O group was observed at wave number of 1684,77 cm-1. The optimum condition for adsorption of Pb2+ ion was obtained at pH 4, contact time 60 min. and adsorption capacity 2.07 mg/g at initial concentration of 10 mg/L. The result showed that Pb2+ ion was adsorbed by Zn-Al-EDTA hydrotalcite according to pseudo second order of reaction with reaction rate 8,90 g mmol-1min-1. Adsorption of Pb2+ ion by Zn-Al-EDTA hydrotalcite happened because of the complex formation between Pb2+ and EDTA in the interlayer space of Zn-Al-EDTA hydrotalcite.